2007
DOI: 10.1111/j.1447-0594.2007.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional tooth number and 15‐year mortality in a cohort of community‐residing older people

Abstract: Background:To study how dental status can become a predictor of overall mortality risk.Methods: Community residents (n = 5730) over 40 years old in the Miyako Islands, Okinawa Prefecture, Japan were followed up for 15 years, 1987-2002. Functional tooth numbers were examined by dentists and overall mortalities of subjects with functional tooth numbers of <10 and 310 were compared in the age groups 40-49, 50-59, 60-69, 70-79 and 80 years or more in both males and females.Results: Groups of 80 years or more showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 21 publications
3
42
0
Order By: Relevance
“…Smoking has considerable influence on the development of clinically detectable periodontitis [79], which eventually over a period of time leads to tooth loss. As smoking is also an important risk factor for allcause and circulatory mortality [80], its non-consideration or rough classification [81,82] may have given rise to an overestimation of tooth number-related effects on mortality in some studies [39,41,43,44,50]. Residual confounding because of smoking has not always been discussed [41,43,44,49,50], although it was known that the relationship between periodontal and cardiovascular disease is prone to this major limitation [83].…”
Section: Confounder Assessment Totalmentioning
confidence: 99%
See 3 more Smart Citations
“…Smoking has considerable influence on the development of clinically detectable periodontitis [79], which eventually over a period of time leads to tooth loss. As smoking is also an important risk factor for allcause and circulatory mortality [80], its non-consideration or rough classification [81,82] may have given rise to an overestimation of tooth number-related effects on mortality in some studies [39,41,43,44,50]. Residual confounding because of smoking has not always been discussed [41,43,44,49,50], although it was known that the relationship between periodontal and cardiovascular disease is prone to this major limitation [83].…”
Section: Confounder Assessment Totalmentioning
confidence: 99%
“…Moreover, the confounder sets of the studies were quite heterogeneous. Few risk models lacked adjustment for clinically relevant confounders such as smoking [39,41] and diabetes [41,46,52] (Tables 3 and 4). Potential residual confounding by smoking was addressed in three studies by performing sensitivity analysis [36], using the number of cigarettes per day for current and former smokers [47], or stratifying by smoking status [56].…”
Section: General Description Of Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fukai et al 4) reported on the mortality of a cohort of community-residing older people. That study indicated that, above the age of 80 years, participants with fewer than 10 functional teeth showed a significantly higher rate of overall mortality than those with 10 PT or more.…”
Section: Discussionmentioning
confidence: 99%